PUF-8, a Pumilio Homolog, Inhibits the Proliferative Fate in the Caenorhabditis elegans Germline - Racher, Hilary (Genetics Society of America, 2012)
Stem cell populations are maintained by keeping a balance between self-renewal (proliferation) and differentiation of dividing stem cells. Within the Caenorhabditis elegans germline, the key regulator maintaining this balance is the canonical Notch signaling pathway, with GLP-1/Notch activity promoting the proliferative fate. We identified the Pumilio homolog, PUF-8, as an inhibitor of the proliferative fate of stem cells in the C. elegans germline. puf-8(0) strongly enhances overproliferation of glp-1(gf) mutants and partially suppresses underproliferation of a weak glp-1(lf) mutant. The germline tumor that is formed in a puf-8(0); glp-1(gf) double mutant is due to a failure of germ cells to enter meiotic prophase. puf-8 likely inhibits the proliferative fate through negatively regulating GLP-1/Notch signaling or by functioning parallel to it.